Evaluation of Acute Oral Toxicity of Ethanol Leaves Extract of Catharanthus roseus in Wistar Albino Rats - Vutukuri, Venkateswar Rao (J Clin Diagn Res, 2017)
INTRODUCTION: Herbal drugs have gained importance globally in the treatment of various diseases. Catharanthus roseus is traditionally used as an anti diabetic and anti cancer drug. To the best of our knowledge limited data are available on acute and sub acute toxicity of C. roseus extract despite its wide spread use in traditional medicine. The present study was under taken to evaluate the acute oral toxicity of the ethanol leaves extract of C. roseus. AIM: To investigate the acute oral toxic effects of ethanol leaves extract of C. roseus. The objective of the study was to evaluate organ toxicity related to heart, liver and kidney in wistar albino rats. MATERIALS AND METHODS: The experiment was done based on the Organization for Economic Co-operation and Development (OECD) guideline 420. The study included twenty five non pregnant female wistar rats (n=25). Sighting study was done using the fixed dose method. The study was conducted by giving a single dose of test drug varying from 5, 50, 300 and 2000 mg and animals were observed for fourteen days. Blood samples were collected and biochemical findings SGPT, SGOT, urea, creatinine, creatinine phosphokinase and Lactate Dehydrogenase (LDH) were analyzed. Food consumption, water intake and histopathology changes were evaluated. RESULTS: Catharanthus roseus Extract (CRE) at a dose of 2000 mg did not produce mortality. SGOT, SGPT, Creatinine phosphokinase, LDH, urea and creatinine were elevated in 300 mg and 2000 mg doses. CONCLUSION: Though there was no mortality, the extract of C. roseus higher than 300 mg can produce signs of biochemical and histopathological toxicity in liver, kidney and heart. It is recommended that lower doses than the studied ones should be used for treatment.